Characteristics of hydrotreated empty fruit bunch after torrefaction for various torrefaction temperatures - Muhammad Hanif Awang Mat Hassan, 1995-, author; Mohd. Faizal Hasan, 1982-, supervisor; Fakulti Kejuruteraan Mekanikal (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2018